Experimental investigation of material extrusion additive manufacturing of copper with high powder loading rate - Jiangtao Li; Zhijie Huang; Bing He; Shuhan Li; Bing Lu; Zemin Wang; Xiangyou Li (Journal of Materials Research and Technology)
Beam-based additive manufacturing has challenges in fabricating pure copper due to high reflectivity. Material extrusion additive manufacturing (MEAM) avoids these issues with low costs, making it suitable to fabricate complex structures in pure copper. In this work, the effects of several printing parameters on the geometry of the samples are studied from single line, thin wall to cube using homemade copper feedstocks with high powder loading rate (65 vol%). The results show that the single line is most affected by layer thickness, while the thin wall has stricter requirements for printing temperature and printing speed. The geometric accuracy of the cube demonstrates large parametric tolerance due to the overlap and support between the lines. Central composite face-centered (CCF) design and central composite design (CCD) are used to analyze and optimize process parameters for densification. The measured porosity at the optimized printing (printing temperature = 177 °C, air gap = −0.05 mm, layer thickness = 0.3 mm) and sintering parameters (sintering temperature = 1045 °C, holding time = 4 h) is in good agreement with the predicted values. Air gap and sintering temperature have the greatest influence on the porosity, and other parameters within a certain range of on-demand adjustments do not have a significant effect. The ultimate tensile strength and elongation of the sintered samples under the optimal parameters are 153.9 ± 6.1 MPa and 31.36 ± 3.24%, respectively. No printing defects are found at the fracture and the elongation is good, showing the effectiveness of the parameter optimization.